Digital marketing strategy and utilization of SWOT analysis to increase agatis brand sales as a brand new stationery - Renny Lubis (Institute of Computer Science (IOCS), 2023)
The development of information technology, especially the internet, provides convenience in all fields, including in the field of marketing, which is known as digital marketing. That is a way of marketing by utilizing social media. By utilizing digital marketing, companies can maximize their promotions without being burdened with large costs and a lot of time, because they can reach a wider audience. This is of course very much needed by Agatis products as new products that are not very well known by the public. Utilization of SWOT analysis is also very much needed because it can analyze the internal factors and external factors of a product in its ability to dominate the market. From this study it was found that there was an effect of digital marketing on increasing sales of Agatis products, it's just that this effect is still small so that in the future it needs special attention to be developed.